Should quinolones come first in therapy? - Marco Berning; Susanne Krasz; Stephan Miehlke (Therapeutic Advances in Gastroenterology, 2011)
New generations of fluoroquinolones, like levofloxacin and moxifloxacin, exhibit a broad-spectrum activity against Gram-positive and Gram-negative bacteria, and have been successfully introduced into the treatment of Helicobacter pylori infection. Based on a large body of evidence, current guidelines recommend the use of levofloxacin- or moxifloxacin-containing proton-pump inhibitor (PPI) triple therapies in second-line or rescue treatment of H. pylori infection. The efficacy of standard PPI triple therapies has substantially declined during the last decade, mainly due to increasing resistance against the key antibiotics clarithromycin and metronidazole. Therefore, alternative strategies for first-line therapy of H. pylori infection have been evaluated in a considerable number of clinical trials including sequential regimens, nonbismuth quadruple regimens, and quinolone-containing PPI triple therapy regimens. The aim of this paper is to summarize the current body of evidence of levofloxacin- and moxifloxacin-containing regimens in first-line treatment of H. pylori infection, and to discuss the risks and benefits of these strategies in the light of increasing resistance of H. pylori to quinolones.